Effect of ethical leadership in corporate tax leaders on corporate transparency, ESG management, and corporate performance - Lee, Eunmi; Kim, Boyoung (International Journal of Management and Sustainability, 2025)
This study aims to empirically assess the effect of ethical leadership in corporate tax leaders on corporate transparency, ESG management, and corporate performance. The research model was constructed, and hypotheses were formulated for structural equation analysis. This study used a total of 262 questionnaires collected from tax leaders in large South Korean companies. A research model was designed using structural equations, and results were derived through confirmatory factor analysis, correlation analysis, and path analysis. The analysis results verified that ethical leadership had a positive effect on corporate transparency and ESG management. However, ethical leadership in tax leaders had no direct impact on corporate performance. This study also proved that this leadership can be positively influenced by corporate transparency and ESG management activities and is not a direct determinant of corporate performance. Additionally, corporate transparency had no direct effect on corporate performance; however, it can be affected along with ESG management as a mediated factor through which the ethical leadership of tax leaders influences corporate performance. These results indicate that the implication is that ethical leadership in corporate tax management impacts corporate performance when corporate transparency and ESG management activities are reinforced, and its effectiveness is maximized as well. Further, it suggests that corporate tax leaders have a crucial role in maintaining financial transparency, fair tax management, and social responsibility.